Certain Second Order Nonlinear differential equations involving k- functions - Vidya H. C. (International Journal of Advanced Science and Technology, 2020)
Ramanujan documented different levels of beautiful Eisenstein series relations in his notebooks. Recently, Shaun Cooper in his book noted several identities involving Eisenstein series and k-functions. In this paper, certain second order nonlinear differential identities have been established, which involves k- functions. Further, the convolution sum has been evaluated using Eisenstein series of level 5 and 10.